Le contrat de concession commerciale et le libre marché - Samson, Claude (Les Cahiers de droit, 1980)
This paper deals with the exclusive sale contract or solus agreement. Its first part identifies some characteristic features of this type of agreement, which quite often is not only aimed at regulating the exercise of trade, but also serves as a technique of market organization and economic power concentration. The impact of the increasing currency of such commercial practices on the free market justifies consideration of the various forms of control that can be exercised by public authorities in order to preserve free competition. Control can be achieved through the judiciary applying concepts such as public order in civil law or public policy at common law. However, in view of the courts' reluctance to interfere with such instances of private economic power and their indifference towards the economic inequities inherent in such agreements for the distributor, legislative intervention has become necessary to protect the free market. Thus the Combines Investigation Act was amended in 1976 to allow regulation of commercial practices such as refusal to deal, consignment selling, exclusive dealing, market restriction and tied selling.